On the Method of Pulse‐Heated Analysis of Solid Reactions (PHASR) for Polyolefin Pyrolysis. Issue 19 (30th December 2020) - Zolghadr, Ali; Sidhu, Nathan; Mastalski, Isaac; Facas, Greg; Maduskar, Saurabh; Uppili, Sundararajan; Go, Tony; Neurock, Matthew; Dauenhauer, Paul J.
Abstract: The continued need for plastics necessitates an effective solution for processing and recycling polymer wastes. While pyrolysis is a promising technology for polyolefin recycling, an experimental apparatus must be designed to measure the intrinsic kinetics and elucidate the chemistry of the plastics pyrolysis process. To resolve this issue, a modified Pulse‐Heated Analysis of Solid Reactions (PHASR) system was designed, constructed, and evaluated for the purposes of polyolefin pyrolysis. Experimental results demonstrated that the new PHASR system is capable of measuring the millisecond‐resolved evolution of plastic [e. g., low‐density polyethylene (LDPE)] pyrolysis products at a constant temperature. The PHASR system was shown to be capable of producing a repeatable, fast heating time (20 ms) and cooling time (130–150 ms), and of maintaining a stable temperature during reaction. A second, Visual PHASR system was developed to enable high‐speed photography and visualization of the real‐time pyrolysis of LDPE. Abstract : Feel the pulse : Pulse‐Heated Analysis of Solid Reactions (PHASR) measures isothermal product evolution kinetics during pyrolysis of plastic waste (low‐density polyethylene). This system is capable of producing a repeatable, fast heating time (20 ms) and cooling time (130–150 ms), and of maintaining a stable temperature during reaction.